2002
DOI: 10.1016/s0896-6273(02)00563-9
|View full text |Cite
|
Sign up to set email alerts
|

Delay between Fusion Pore Opening and Peptide Release from Large Dense-Core Vesicles in Neuroendocrine Cells

Abstract: Peptidergic neurotransmission is slow compared to that mediated by classical neurotransmitters. We have studied exocytotic membrane fusion and cargo release by simultaneous capacitance measurements and confocal imaging of single secretory vesicles in neuroendocrine cells. Depletion of the readily releasable pool (RRP) correlated with exocytosis of 10%-20% of the docked vesicles. Some remaining vesicles became releasable after recovery of RRP. Expansion of the fusion pore, seen as an increase in luminal pH, occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
204
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(228 citation statements)
references
References 48 publications
22
204
2
Order By: Relevance
“…Note the two distinct phases of the response to glucose Ca 2+ concentration are usually monophasic or oscillatory [72]. As regards (ii) and (iii), electron microscopy showed that the morphologically docked pool comprised several hundred vesicles, a quantity significantly greater than the maximum number of vesicles in the readily releasable pool (~15) [71], although only a tiny fraction of the total beta cell vesicle complement (~13,000). Nevertheless, recent data in neurones [73] suggest that readily releasable vesicles are not localised close to the presynaptic membrane, but are instead dispersed through the vesicle cluster.…”
Section: Glucose-stimulated Insulin Secretion Is Biphasic: Visualisatmentioning
confidence: 98%
See 1 more Smart Citation
“…Note the two distinct phases of the response to glucose Ca 2+ concentration are usually monophasic or oscillatory [72]. As regards (ii) and (iii), electron microscopy showed that the morphologically docked pool comprised several hundred vesicles, a quantity significantly greater than the maximum number of vesicles in the readily releasable pool (~15) [71], although only a tiny fraction of the total beta cell vesicle complement (~13,000). Nevertheless, recent data in neurones [73] suggest that readily releasable vesicles are not localised close to the presynaptic membrane, but are instead dispersed through the vesicle cluster.…”
Section: Glucose-stimulated Insulin Secretion Is Biphasic: Visualisatmentioning
confidence: 98%
“…Three theories have been proposed: (i) time-dependent changes in the concentration of signalling molecules [69]; (ii) physical recruitment of vesicles from a reserve to a readily releasable pool [70]; and (iii) recruitment of vesicles to a readily releasable pool by other mechanisms (e.g. covalent modification of a vesicle protein) [71]. isoforms of each AMPK subunit exist [64].…”
Section: Glucose-stimulated Insulin Secretion Is Biphasic: Visualisatmentioning
confidence: 99%
“…3). In B-cells, the size of the burst that can be released immediately upon Ca 2π -influx corresponds to less than 1% of the total number of granules (Barg et al 2001a(Barg et al , 2002a. Refilling of this functionally defined ''readily releasable pool'' is ATP-, Ca 2π -and temperature-dependent (Bittner & Holz 1992;Parsons et al 1995, Renström et al 1996a& b, Eliasson et al 1997Gromada et al 1999), and commonly referred to as ''priming'' (Hay & Martin 1992).…”
Section: Docking Priming Atp-dependence and Kinetics Of Exocytosismentioning
confidence: 99%
“…Refilling of this functionally defined ''readily releasable pool'' is ATP-, Ca 2π -and temperature-dependent (Bittner & Holz 1992;Parsons et al 1995, Renström et al 1996a& b, Eliasson et al 1997Gromada et al 1999), and commonly referred to as ''priming'' (Hay & Martin 1992). In the B-cells, the ''readily releasable pool'' can be depleted in less than a second (Barg et al 2001a(Barg et al & 2002a, whereas its refilling takes up to a minute Barg et al 2002a). Under conditions of prolonged stimulation, the priming of vesicles for exocytosis therefore becomes rate-limiting, which may account for the biphasic time course in glucose-stimulated insulin secretion.…”
Section: Docking Priming Atp-dependence and Kinetics Of Exocytosismentioning
confidence: 99%
See 1 more Smart Citation